2001
DOI: 10.1128/jb.183.18.5334-5342.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Rhizobium lupini H13-3 and Sinorhizobium meliloti Flagellin Genes: Importance of Flagellin A for Flagellar Filament Structure and Transcriptional Regulation

Abstract: Motile bacteria are propelled by helical flagellar filaments connected by a proximal hook to the basal body holding the flagellar rotary motor (for reviews, see references 1, 20, and 41). Traditionally, flagellar filaments are classified by their electron microscopical appearance into two types, named plain and complex (22,33). The plain filaments of Escherichia coli and Salmonella spp. have a smooth surface structure with faint striations, whereas the complex filaments of soil bacteria, like Rhizobium lupini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 39 publications
2
105
0
4
Order By: Relevance
“…The cells were allowed to sediment to carbon-coated grids for 1-2 min. After negative staining with 1 % uranyl acetate, the grids were examined with a Philips CM12 transmission electron microscope (Scharf et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were allowed to sediment to carbon-coated grids for 1-2 min. After negative staining with 1 % uranyl acetate, the grids were examined with a Philips CM12 transmission electron microscope (Scharf et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Unlike E. coli, the soil bacterium S. meliloti is driven by rather rigid, righthanded helical filaments, which facilitate efficient swimming in a viscous environment (Go$ tz et al, 1982). Whereas the ' plain ' enterobacterial flagellar filaments are assembled from monomeric flagellin subunits, the ' complex ' rhizobial filaments consist of four related flagellin subunits that are assembled as functional heterodimers (Scharf et al, 2001). The complex flagellar fine structure is dominated by three helical ribbons that lock the filament in right-handedness, thus blocking a switch of hand (Cohen-Krausz & Trachtenberg, 1998).…”
Section: Swimming Patterns and Flagellar Rotary Controlmentioning
confidence: 99%
“…In S. meliloti and the related Rhizobium lupini H13-3 (Scharf et al, 2001), rotary speed variation of the flagellar motor has a molecular corollary in two new motility proteins, MotC and MotD (Platzer et al, 1997), present in addition to the ubiquitous MotA\MotB transmembrane proteins that form the energizing proton channels (Fig. 1).…”
Section: Swimming Patterns and Flagellar Rotary Controlmentioning
confidence: 99%
“…It has been suggested that the direction of movement is reversed by changes in flagellar rotational speed (Sourjik & Schmitt, 1996;Miller et al, 2007). This type of flagellar movement is thought to be an adaptation of the rhizobia to the specific condition of swimming in viscous fluids that is prevalent in the soil (Scharf et al, 2001). …”
Section: Introductionmentioning
confidence: 99%